Trajetórias de acadêmicas no Brasil e em Portugal: um olhar sobre o gênero a partir de uma Grounded Theory - Soares, Eva Bessa (2019)
This research inserts itself in the purview of gender relations in academia. The objective was to seize the perceptions of lecturers/researchers on the specificities of being women and to develop a career in the work context of Administration (Brazil) and Management (Portugal). We support this on studies regarding the underrepresentation of women in science and academia in positions of power and decision, horizontal and vertical segregations of women in academia overall and in Administration. The theoretical input was also composed by the studies on the challenges faced by the lecturers for the management of the time needed to the assignments of the profession and the time required to the domestic tasks and care of the children, the context of the institutional incentive's concessions to aid the management of the balance between work and personal/family life, the high demands of individual actions for the balance between work and personal life and its consequences for health, female empowerment and others. The methodological approach used was the qualitative substantiated on the data (Grounded Theory), based on Strauss and Corbin (2008). The data were obtained from the collection of narratives of 33 lecturers/researchers working in graduate programs (sensu stricto) in the field of Administration (Brazil) and Management (Portugal). Of this group, 18 are Brazilian and the other Portuguese. When we hear the lecturers/researchers in this field of knowledge, it was possible to know their perceptions about what it is like to be women and to develop academic careers in this field. We point out in the conclusions that in the studied context there are discriminations regarding gender, although not all the interviewees perceive them and report in the same way. This discussion is important because, although women have high levels of schooling, they are still underrepresented in academy's high positions. This phenomenon leads us to infer that this context is marked by discriminatory and excluding relations. The debate must always be present in the academy to think ways to minimize or even extinguish such impacts on women's careers.